Insights from multi-process fan deposits in martian intracrater basins on post-Noachian climate change - Williams, Rebecca M. E. (Frontiers in Astronomy and Space Sciences, 2025)
Alluvial fans are a sensitive record of environmental transitions. Prior studies have determined that martian fans are primarily located in impact crater basins and that fan deposition occurred principally between 3.7 and 3.3 Ga or later, corresponding to the presumed critical climate-changing period. This paper illustrates previously unrecognized flow types and superposition relationships in fan deposits that show a time sequence of varying processes. Examples include debris flows following earlier eroded fluvial deposits (ridges interpreted as inverted channels), an intriguing pitted deposit interpreted to be a highly viscous mudflow with air bubble release, and landforms recording the role of late-stage fluvio-glacial processes. The diversity of fan forms highlight the complex and variable conditions on post-Noachian Mars. This evidence supports fluctuating ‘warm, wet’ and ‘cold, dry’ periods, suggesting that the climate transition was variable and slowly degraded, rather than a swift monotonic decline.